Policy preferences for inheritance taxation - Ivo Bischoff; Nataliya Kusa (Philipps-University Marburg, School of Business and Economics, 2015)
We provide a comprehensive empirical study on the factors that drive citizens' policy preferences regarding inheritance taxation. It builds on a representative survey among more than 1.000 German citizens in 2014 and 2015. Support for inheritance taxation is found to be driven by monetary self-interest and redistributive preferences. It is lower among females and among subjects who overestimate the tax burden. We look beyond the narrow scope of inheritances and account for other forms of transfers in the family, in particular the provision of longterm care. More than 75 percent of our respondents consider it fair that family members who provided long-term care receive higher inheritances in exchange. This fairness preference does not drive policy preferences, but acceptance for inheritance taxation is higher among subjects who expect the typical German family to reward intrafamilial care-giving through a higher inheritance.
Keywords: H27; D31; D72; 330; inheritance taxation; intergenerational transfers; citizens' preferences; longterm care; vignettes